Penerapan Konsep Tri Hita Karana dalam Hubungannya dengan Budaya Organisasi di Rektorat UNUD - Putera, I Dewa Gede Wahyudi; Supartha, Wayan Gede (E-Jurnal Manajemen; Vol 3 No 7 (2014), 2014)
The purpose of this study was to reveal the descriptive overview of Tri Hita Karana at Udayana University rectorate and determine the effect of Tri Hita Karana at Udayana University rectorate . This research was conducted at Udayana University Rector , number of samples taken as many as 59 people , with a proportionate stratified random sampling technique data analysis techniques using factor analysis . From the analysis we found that organizational and cultural conditions in the Tri Hita Karana is good and the Rector of Udayana University Tri Hita Karana influence on organizational culture To improve the organizational culture needs to encourage employees to help solve the problems of society and the environment in which to work , motivated to want to exchange ideas for the development and advancement of education , have a program to rescue and preservation of the environment sertamemiliki health facilities for their employees and provide guidance and empowerment for improving the welfare of society local and traditional organizations around campus also need to carry out periodic Tirta Yatra   keyword : tri hita karana, management, culture organization // " class="_mp3rocket_overlay_style" style="left: ; top: ; width: ; height: "> // ]]> // " class="_mp3rocket_overlay_style" style="left: ; top: ; width: ; height: "> // ]]>